Educação como autonomia em Agostinho e Paulo Freire - Souza, Adailson Nascimento (2024)
This thesis aims to investigate education as autonomy in Agostinho and Paulo Freire, focusing on a conceptual treatment of interiority, from Agostinho, and autonomy, from Freire. This is a qualitative research, using a dense bibliographic review and documentary analysis, with the theoretical reference being the base of the bibliography consulted. In the construction of the research report a study is presented on the historical milestone of the presence of autonomy in the context of Brazilian education, in which education and the curriculum begin to be disputed as a device of cultural overcoming in the construction of autonomy; in a second moment, the contributions of Enrique Dussel are used as theoretical and bibliographical references, with special attention to the concept of political autonomy; and the concept of educational autonomy, by Paulo Freire, is studied as a driving force for the potential of human autonomy. The thesis concludes with an analysis of education as autonomy in Agostinho and Paulo Freire, in which the proposal of education and curriculum as autonomy in Agostinho is developed more specifically, with his work De Magistro being the foundation of the analysis of the concept of interior man where autonomy takes place. This research aims to clearly defend that education can build autonomy in the subject, a thesis based on the indicated referential, without disregarding the influences of their respective social, historical and cultural contexts